PROGNOSTIC VALUE OF ADP-INDUCED PLATELET AGGREGATION IN PEPTIC ULCER–RELATED GASTROINTESTINAL BLEEDING AMONG PATIENTS RECEIVING ANTIPLATELET THERAPY (Vietnam Journal of Community Medicine, 2026)
Background: Gastrointestinal bleeding (GIB) is a severe and common complication in patients receiving antiplatelet therapy. Excessive platelet inhibition, reflected by adenosine diphosphate (ADP)-induced platelet aggregation testing, may significantly increase bleeding risk. This study aimed to evaluate the relationship between the degree of platelet inhibition (ADP%) and the severity of peptic ulcer–related GIB in patients taking antiplatelet agents.Methods: A prospective observational study was conducted on 32 patients with peptic ulcer–related GIB who were taking aspirin and/or clopidogrel. ADP testing was performed within 24 hours of hospital admission using the LTA system. Clinical parameters, including hemoglobin (Hb), Rockall score, Glasgow–Blatchford score (GBS), and transfused blood volume, were analyzed in relation to ADP values.Results: The mean ADP value was 38.5 ± 15.2%. Patients with ADP
Keywords: Gastrointestinal Hemorrhage, Peptic Ulcer, Platelet Aggregation Inhibitors, Adenosine Diphosphate, Platelet Function Tests, Risk Assessment